The organization of Chilean political refugees in Mendoza and the hunger strike of July 1976 - Paredes, Alejandro (2012)
This article focuses on the situation of Chilean political refugees in Mendoza (Argentina) between 1976 and 1983. In that period they were persecuted by dictatorships of Chile and Argentina. 2,539 families (6,899 people) unable to get out of Mendoza, were assisted by an organization created by Christian churches called Comité Ecuménico de Acción Social (CEAS). It was fi nanced by the World Council of Churches and the High Commissioner for Refugees. Driven Alejandro Paredes by desperation, the Chilean refugees staged a hunger strike in 1976. This revealed the serious situation of refugees and persecution suffered by the CEAS.